Payments for ecosystem services in Hoa Binh province, Vietnam: an institutional analysis - Tran, T.T.H.; Zeller, M.; Suhardiman, Diana (2016)
This study examines the institutional design and actual performance, of payments for ecosystem services (PES) in Vietnam. Taking Payments for Forest Environmental Services Program (PFES Program) implementation in Da Bac district, Hoa Binh province as a case study, it brings to light how PES program design and implementation contributed to the central government's objectives to: (1) involve stakeholders in forest management; (2) reduce the government's budget burden for forest protection; and (3) maintain political control over forest resources. In Vietnam, the PFES Program is implemented in a top-down manner. Participating households act as government-induced forest guards rather than forest owners. Incomplete design at the central-level results in poorer performance at lower levels and, the lack of strategic management makes it difficult to know whether the program has actually improved ecosystem services and forest management. While the PFES Program complements other institutions at the national- and local-levels, some institutional incompatibilities exist in terms of customary practices. It is unlikely, however, that these will develop into an institutional conflict.